A Study on Thyroid Stimulating Hormone Levels among Pregnant Women (Ibrahim Cardiac Medical Journal, 2026)
Background & objective: The thyroid gland is critical for maintaining metabolism and ensuring normal fetal neurological development. A deficiency of thyroid hormone during pregnancy can lead to irreversible neurological deficits and mental retardation in the child. Maternal hypothyroidism can also cause pregnancy complications such as pre-eclampsia and preterm delivery. The present study was designed to screen for maternal hypothyroidism by assessing serum thyroid-stimulating hormone (TSH) levels in pregnant women during their second and third trimesters.Methods: This cross-sectional study was conducted at the Antenatal Clinic of Mymensingh Medical College Hospital from September 2004 to June 2005. A total of 100 pregnant women in their second and third trimesters were consecutively included. Serum TSH was measured using an immunoradiometric assay. For participants in the 2nd and 3rd trimesters, TSH levels below 0.2 mIU/L and above 3.0 mIU/L were considered decreased and raised respectively.Results: The mean age of the participants was 25.4 ± 5.1 years. A majority (82%) of the women were in their third trimester. The mean serum TSH level was 1.90 ± 1.32 mIU/L. The study found that 96% of the pregnant women had normal TSH levels, while 3% had decreased and 1% had raised TSH levels. The distribution of participants by trimester showed a strong skew towards the third trimester, with 82% of women in their third trimester and 18% in their second trimester. Conclusion: The findings suggest that the prevalence of abnormal TSH levels in pregnant women visiting the Mymensingh Medical College Hospital antenatal clinic is low. However, the high proportion of women attending their first antenatal visit in the third trimester underscores the need for public awareness campaigns to encourage earlier prenatal care. A comprehensive screening program for pregnant mothers is recommended to ensure timely diagnosis and treatment, thereby preventing potential adverse outcomes for both the mother and the fetus.Ibrahim Card Med J 2024; 14 (2): 32-36